MODEL CERITA FIKSI KONTEMPORER ANAK-ANAK UNTUK PENGEMBANGAN KEMAHIRWACANAAN SISWA KELAS 5 SEKOLAH DASAR - Muakibatul Hasanah (LITERA, 2012)
This study aims to find a model for children’s contemporary fiction to improve the literacy of the fifth grade students of elementary schools. It employed a qualitative hermeneutics design. The data resources were children’s contemporary fiction books and responses of the fifth grade students of elementary schools. The data were collected through content analysis and analytic reflection. The findings show that: (a) the students’ responses are positive; (b) the books have a single, simple, and linear plot/narrative structure, have a dramatic and narrative style, and have various themes and values; and (c) children’s contemporary fiction contributes to the literacy improvement.